Applications of neutron spin echo in soft matter - Luo, Xiang; Cui, Tengfei; Chu, Xiangqiang (Frontiers in Physics, 2023)
Soft matter systems exhibit diversity and intricacy in their structures and properties, with their dynamic behaviors and structural changes spanning wide time and length scales. Gaining insight into the internal structures and dynamics behaviors of soft matter systems, as well as the interactions among molecules and particles, contributes to a deeper comprehension of the microscopic behaviors of matter. Moreover, this endeavor has significant biomedical and materials engineering implications. This review focuses on the applications of spin-echo small-angle neutron scattering (SESANS) and high-resolution neutron spin-echo (NSE) spectroscopy in soft matter science, particularly complex fluids and biomolecular systems. NSE spectroscopy has remarkable temporal resolution and sensitivity towards molecularscale dynamic behaviors. Therefore, it provides comprehensive insights into microscale dynamic phenomena to soft matter systems, such as the rheological behaviors, stability, and aggregation dynamics of colloids; the domain dynamics and conformational changes of proteins; the collective dynamics of lipid membranes and interactions with other molecules, as well as the dynamic behaviors and interactions of surfactants within microemulsions. NSE technique helps reveal the complex nature of these systems, providing valuable insights into advances in materials science, biomedicine, and chemistry.